Geographic disparities in donor lung supply and lung transplant waitlist outcomes: A cohort study. Issue 6 (27th January 2018) - Benvenuto, Luke J.; Anderson, David R.; Kim, Hanyoung P.; Hook, Jaime L.; Shah, Lori; Robbins, Hilary Y.; D'Ovidio, Frank; Bacchetta, Matthew; Sonett, Joshua R.; Arcasoy, Selim M.; ,
Abstract : Despite the Final Rule mandate for equitable organ allocation in the United States, geographic disparities exist in donor lung allocation, with the majority of donor lungs being allocated locally to lower‐priority candidates. We conducted a retrospective cohort study of 19 622 lung transplant candidates waitlisted between 2006 and 2015. We used multivariable adjusted competing risk survival models to examine the relationship between local lung availability and waitlist outcomes. The primary outcome was a composite of death and removal from the waitlist for clinical deterioration. Waitlist candidates in the lowest quartile of local lung availability had an 84% increased risk of death or removal compared with candidates in the highest (subdistribution hazard ratio [SHR]: 1.84, 95% confidence interval [CI]: 1.51‐2.24, P  < .001). The transplantation rate was 57% lower in the lowest quartile compared with the highest (SHR: 0.43, 95% CI: 0.39‐0.47). The adjusted death or removal rate decreased by 11% with a 50% increase in local lung availability (SHR: 0.89, 95% CI: 0.85‐0.93, P  < .001) and the adjusted transplantation rate increased by 19% (SHR: 1.19, 95% CI: 1.17‐1.22, P  < .001). There are geographically disparate waitlist outcomes in the current lung allocation system. Candidates listed in areas of low local lung availability have worse waitlist outcomes. Abstract : Using the arbitrary borders of donation service areas as the primary unit of lung allocation results in geographically disparate waitlist outcomes.